Hypermedia-based Web Services as System Integrators - Teixeira, Luciano de Castro Oliveira Brochado (2015)
As we move more closely to the practical concept of the Internet of Things and, our reliance on public and private APIs increases, web services and their related topics have become utterly crucial to the informatics community. However, the question about which style of web services would best solve a particular problem, can raise signi cant and multifarious debates. There can be found two implementation styles that highlight themselves: the RPC-oriented style represented by the SOAP protocol’s implementations and the hypermedia style, which is represented by the REST architectural style’s implementations. As we search examples of already established web services, we can nd a handful of robust and reliable public and private SOAP APIs, nevertheless, it seems that RESTful services are gaining popularity in the enterprise community. For the current generation of developers that work on informatics solutions, REST seems to represent a fundamental and straightforward alternative and even, a more deep-rooted approach than SOAP. But are they comparable? Do both approaches have each speci c best suitable scenarios? Such study is brie y carried out in the present document’s chapters, starting with the respective background study, following an analysis of the hypermedia approach and an instantiation of its architecture, in a particular case study applied in a BPM context.